2001
DOI: 10.1007/s003930170004
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral analgesic and antiinflammatory effects of opioids

Abstract: Traditionally, opioids were considered the prototype of centrally acting analgesics. In the past decade a substantial literature has emerged demonstrating that opioids can produce potent and clinically measurable analgesia by activation of opioid receptors on peripheral terminals of primary sensory neurons. In addition, endogenous ligands of these peripheral receptors were discovered in immune cells. Major recent findings in peripheral opioid analgesia include the relative lack of tolerance under inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 83 publications
2
46
0
3
Order By: Relevance
“…However, even at these dose levels, we could clearly discriminate the effects of s.c. morphine in the different experimental conditions. Doses of morphine that induced antinociception also produced inhibition of plasma extravasation with a biphasic response that has been reported previously by our group and others (Stein et al, 2001a;Romero et al, 2005). The dual response could be related to high-and low-affinity states of the MOR or to different functional subtypes or splice variants of the receptors (Pasternak, 2001).…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365supporting
confidence: 78%
“…However, even at these dose levels, we could clearly discriminate the effects of s.c. morphine in the different experimental conditions. Doses of morphine that induced antinociception also produced inhibition of plasma extravasation with a biphasic response that has been reported previously by our group and others (Stein et al, 2001a;Romero et al, 2005). The dual response could be related to high-and low-affinity states of the MOR or to different functional subtypes or splice variants of the receptors (Pasternak, 2001).…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365supporting
confidence: 78%
“…10 Although there is a ceiling effect on the degree of analgesia attainable with the peripheral administration of opioids, benefits of this route include the anti-inflammatory effects of and agonists and a lack of tolerance under conditions of inflammation. 11 One study suggested the receptor to be the predominant opioid receptor found in the lung. 12 An additional mechanism for the therapeutic effects of inhaled morphine might be the inhibition of pulmonary-irritant receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the supraspinal and spinal localization, opioid receptors have been found in peripheral nerves, and peripherally injected opiates produce potent analgesia in acute pain models (Coggeshall et al, 1997;Dionne et al, 2001;Stein et al, 2001). Peripheral morphine is reported to have potent antinociceptive effect under inflammatory conditions (Stein et al, 1988).…”
mentioning
confidence: 99%